THE SIGNIFICANCE OF PRE-MARRIAGE COURSES IN THE PERSPECTIVE OF ISLAMIC COMMUNITY DEVELOPMENT - Fatoni, Muhammad Syaidi; Nasor, M.; Jasmadi, Jasmadi (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2023)
The Ministry of Religious Affairs has formulated the Regulation of the Director General of Islamic Public Guidance No. DJ.II/542 of 2013 concerning Guidelines for the Implementation of Pre-Marriage Courses, which are applied at the Office of Religious Affairs of Tanjung Karang Timur District. This research aims to know how far the level of significance of pre-marriage courses is to people of marriageable age as a form of increasing understanding of the community from the perspective of Islamic community development. The approach used is a qualitative approach. Data is sourced from primary, secondary, and population and sample data. The population is 16 pairs of prospective brides or 32 people, and the sample is 8 pairs of prospective brides or 16. With data collection techniques such as interviews, observation, documentation, and data analysis. Based on the results from research on the implementation of pre-marital courses and the processes carried out, it can be concluded that pre-marital courses are beneficial and necessary for the community. Community development aims to improve the quality of life of the community through the awareness process, the capacity-building process, and the enrichment process. It is significant for creating a Sakinah family.